Raising the level for $\def \xmlpi #1{}\def \mathsfbi #1{\boldsymbol {\mathsf {#1}}}\let \le =\leqslant \let ≤ =\leqslant \let \ge =\geqslant \let ≥ =\geqslant \def \Pr {Pr}\def \Fr {Fr}\def \Rey {Re}\text {GL}_{{n}}$. (10th June 2014) - THORNE, JACK A.
Abstract: We prove a simple level-raising result for regular algebraic, conjugate self-dual automorphic forms on $GL_n$ . This gives a systematic way to construct irreducible Galois representations whose residual representation is reducible.